2014
DOI: 10.1186/1471-2180-14-45
|View full text |Cite
|
Sign up to set email alerts
|

Scale-up of anaerobic 1,3-propanediol production by Clostridium butyricum DSP1 from crude glycerol

Abstract: BackgroundAs the production of biofuels from raw materials continuously increases, optimization of production processes is necessary. A very important issue is the development of wasteless methods of biodiesel production. One way of utilization of glycerol generated in biodiesel production is its microbial conversion to 1,3-PD (1,3-propanediol).ResultsThe study investigated the scale-up of 1,3-PD synthesis from crude glycerol by Clostridium butyricum. Batch fermentations were carried out in 6.6 L, 42 L and 150… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 55 publications
1
25
0
Order By: Relevance
“…As described by Zhang et al and Zeng et al, 1,3‐PDO production was an NADH‐needing process, and the NADH came from glycerol oxidative pathways which would synthesize acids, such as butyric acid and acetic acid, finally. Szymanowska‐Powalowska and Białas reported that 1,3‐PDO bioconversion process could be influenced by osmotic stress (high concentrations of glycerol), toxic stress (high concentrations of organic acids and 1,3‐PDO), mechanical stress and oxidative stress. Biebl and Szymanowska‐Powalowska also presented the similar findings that high concentration of butyric acid and acetic acid inhibited the production of 1,3‐PDO by C. butyricum when pH was maintained at 6.5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As described by Zhang et al and Zeng et al, 1,3‐PDO production was an NADH‐needing process, and the NADH came from glycerol oxidative pathways which would synthesize acids, such as butyric acid and acetic acid, finally. Szymanowska‐Powalowska and Białas reported that 1,3‐PDO bioconversion process could be influenced by osmotic stress (high concentrations of glycerol), toxic stress (high concentrations of organic acids and 1,3‐PDO), mechanical stress and oxidative stress. Biebl and Szymanowska‐Powalowska also presented the similar findings that high concentration of butyric acid and acetic acid inhibited the production of 1,3‐PDO by C. butyricum when pH was maintained at 6.5.…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, owing to the longer time of feeding in fed‐batch fermentation process, the productivity of 1,3‐PDO in batch fermentation strategy was higher, while the concentration of 1,3‐PDO was higher than that in batch process. Chatzifragkou et al and Szymanowska‐Powalowska and Białas selected strains with high performance of 1,3‐PDO production (70.8 g/L and 71 g/L respectively) through fed‐batch strategy. Compared with processes above, whether in batch or fed‐batch process, the adaptive evolution strain could not only obtain the same excellent performance in 1,3‐PDO production (66.23 g/L), but also consume less time with better productivity.…”
Section: Resultsmentioning
confidence: 99%
“…The biotechnological methods that have been designed to obtain 1,3-PD by converting glycerol use the bacteria of the genera Clostridium, Klebsiella, Citrobacter, Hafnia, Lactobacillus [6,7,8]. In the process of selecting a 1,3-PD producer, consideration must be given not only to such vital features as resistance to osmotic, toxic, and mechanical stresses or maintenance of growth capability under the conditions of industrial-scale synthesis but also to an appropriate cultivation method [9,10]. The choice of a culturing protocol is mainly determined by the cost of fermentation medium (substrate included) and by process specifications, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Fermentative production of 1,3-PDO by C. butyricum has been extensively studied and achieved success in repeated batch, two-stage temperature control, and immobilization system in the past decades. 7,13,14 However, many byproducts have a negative effect which come from osmotic stress, toxic stress, and feedback inhibition 15 on growth and 1,3-PDO production. The relatively low 1,3-PDO content in the final product is still a major barrier that limits the product quality and scale-up.…”
Section: Introductionmentioning
confidence: 99%